Design of a polymer 3D-thermal accelerometer - Silva, C. S. (2011)
A completely new approach for the fabrication of 3-axis thermal accelerometers is presented in this paper. Microinjected polystyrene micro-parts are assembled with active polyimide membranes enabling the construction of an innovative polymer based thermal accelerometer. The use of polymers (polystyrene and polyimide) with low thermal conductivities improves the overall power consumption of the thermal accelerometer and enables a simple and low-cost fabrication process (no clean room infrastructure required).